Synthesis of Aryl- and Alkylquinones through Rhodium-Catalyzed C–C Coupling under Mild Conditions - Wang, Dawei; Ge, Bingyang; Du, Liyong; Miao, Hongyan; Ding, Yuqiang (Synlett, 2014)
A direct arylation, alkylation of quinones with aryl and alkyl boronic acids through rhodium-catalyzed C–C coupling has been developed under mild conditions. [Cp*RhCl2]2 was shown to be the most effective catalyst for the transformation. More importantly, good to excellent yields were obtained under room temperature and base-free conditions. This reaction provides a practical, efficient method for the synthesis of aryl- and alkylquinones.
Keywords: arylation; alkylation; quinones; rhodium; coupling